Parents' Leisure, LGB Young People and "When We Were Coming Out". (2nd January 2017) - Trussell, Dawn E.
ABSTRACT: This article examines parents' leisure experiences in relation to their child's coming out process and developing lesbian, gay, and bisexual (LGB) identity. Thirteen heterosexual-identifying parents (seven mothers and six fathers) from Canada and the United States were interviewed about the social context and relational aspects of their leisure experiences (e.g., special events and holidays, friends, co-participants, co-workers). Analysis showed that leisure contexts could be altered in relation to their child's developing LGB identity and cultural norms related to heterosexism and homophobia. Three main themes that best reflected the mothers' and fathers' experiences emerged: (a) grieving heterosexist ideals and reframing familial expectations, (b) encountering homophobia and the loss of community, and (c) coming out of the family home and creating a supportive network.